Maxillary esthetic correction using hybrid prosthesis with precision attachment: Koreksi estetik rahang atas menggunakan prostesis hybrid dengan kaitan presisi - Astri Al hutami Aziz; Riezky Rhamdani; Bahruddin Thalib (Makassar Dental Journal PDGI Makassar, 2024)
Replacement of missing teeth should be done with several considerations including retention. The use of precision anchorage is an appropriate alternative choice for patient comfort. A precision link is a small interlocking device to connect the denture to the abutment teeth that can provide biomechanical and aesthetic benefits. A 56-year-old woman came to Hasanuddin University Oral and Dental Hospital because she could not chew food properly and wanted a denture made. The patient had partial loss of upper and lower teeth, and felt some upper teeth were loose. The loose teeth were extracted and the remaining teeth 13,12,11, 21,23 were made into a longspan bridge and the edentulus part was made into a metal frame denture with precision links. The use of precision cusps in bilateral free end maxillary aesthetic correction cases using a combination of fixed and removable den-tures is one of the best treatments other than implants. It is concluded that precision linking significantly improved denture reten-tion and patient comfort. The combined treatment option of using a fixed and removable denture in this case provided a better aesthetic appearance as well as improved function and favourable retention.